The Natural Lighting Performance Simulation in The Heritage Building: A Case Study of Gedung Singa Surabaya - Wijaya, Elvina Shanggrama; Dharmatanna, Stephanus Wirawan; Tan, Novela Cleine (Institut Teknologi Adhi Tama Surabaya, 2025)
The ‘Gedung Singa’ in Surabaya is one of the first buildings in Indonesia, designed by renowned Dutch Architect, Hendrik Petrus Berlage in 1901. Despite having historical significance equal to that of the surrounding historical building, Gedung Singa appears to be vacant and ill-maintained. In recent years, the Surabaya City Government has already made efforts to revive Surabaya's old city area. Aligning with this attempt, this research aims to model the Gedung Singa via digital architecture software and do simulation to picture the daylight potential use of the building. This research found that the Gedung Singa is well adapted to the tropical climate, which results in reducing the amount of direct natural light penetrating the indoor area of the building, which further, will also reduce the heat load. Then, a more intensive simulation was carried out to optimize the existing bounced natural light to spread the illumination more evenly throughout the indoor areas of the building.